The Impact of Apple Cider Vinegar on Insulin Resistance and Related Conditions: Benefits, Mechanisms, and Potential Risks - Literature Review - Kadłubek, Sabina; Mąka, Magdalena; Kalinowski, Szymon; Woźniak, Julia; Kapturska, Natalia; Cymerys, Kinga; Kardaszewski, Piotr; Kamiński, Jakub; Sikora, Dominik; Zielnik, Martyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: The topic of apple cider vinegar supplementation and insulin resistance is becoming increasingly widespread, especially on the internet, which carries many potential risks. There is a need to understand both how apple cider vinegar reduces insulin resistance and improves metabolic parameters, as well as the potential risks of its use. Material and methods: Medical databases like PubMed, Google Scholar, and Embase were searched for scientific papers on the safety, benefits, mechanisms, and risks of apple cider vinegar in insulin resistance and related conditions. These were analyzed and summarized in a single review. State of knowledge: Apple cider vinegar supplementation contributes to a reduction in insulin resistance, which is reflected in parameters such as decreased postprandial insulin secretion, lower levels of triglycerides (TG) and total cholesterol (TC), reduced fasting glucose, lower HbA1c levels, and supports weight loss, potentially improving insulin sensitivity. In most cases, no adverse effects or serious side effects were observed with doses of 15-30 ml per day. However, potential risks include delayed gastric emptying, exacerbation of gastroesophageal reflux disease (GERD), gastrointestinal disturbances, tooth erosion, although one study suggests that such supplementation may be associated with acute pancreatitis. Conclusions: More research is needed on supplementation, particularly regarding its duration. Another risk is the search for health information online without critically evaluating the content. Weight loss through a proper diet and exercise appears to be key for improving insulin sensitivity, but supplementation may help achieve results in certain patient groups.